Assessing Malaysia’s urban security through Emerging Hot Spot Analysis (EHSA): A spatiotemporal investigation of burglary patterns within police jurisdictions of Selangor, Kuala Lumpur, and Putrajaya, Malaysia - M.S. Redzuan; T. Masron; A. Ahmad; K.K. Abdillah; A. Yusuf; S.N. Junaini; M.A.H. Jamian; Y. Kimura; R. Rainis; Norita Anak Jubit (Geoinformatics International, 2025)
This study investigates the spatiotemporal patterns of midnight burglary (12 am–6:59 am) across 84 Police Station Boundaries (PSBs) in Selangor, Kuala Lumpur, and Putrajaya using Emerging Hot Spot Analysis (EHSA). The research addresses critical issues in urban crime dynamics, particularly the impact of the COVID19 pandemic on burglary trends. The objectives include identifying intensifying, diminishing, and other hotspot categories to enhance understanding of spatial crime distributions. A spatiotemporal design, utilizing advanced GIS tools, classifies crime hotspots into nuanced categories, enabling a comprehensive analysis of burglary trends from 2015–2020. Findings reveal significant disparities in burglary intensification in areas such as Kajang (8.60%), Selayang (4.73%), and Klang (4.56%), with diminishing trends observed in regions like Sri Muda. Oscillating and emerging patterns were noted in Kuang and Rawang. Conclusions emphasize the need for targeted, evidence-based law enforcement strategies to mitigate crime risks effectively. The study underscores implications for collaborative urban security policies, advocating for adaptive resource allocation and strategic interventions amidst evolving socio-economic disruptions. This work contributes to criminological literature by demonstrating the utility of EHSA in spatiotemporal crime analysis and informing public safety initiatives.